Pembentukan Karakter Pada Anak Usia Dini Melalui Kegiatan Ruang Kreatif di Homeschooling Pena Surabaya - Reziana Firdaus; Maria Veronika Roesminingsih (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Character building is a process carried out by education to instill basic character values ??in students and be able to build good character. This study aims to determine the formation of character and the formation of character values ??in early childhood through creative space activities at Homeschooling Pena Surabaya. The method used in this research is descriptive qualitative research. Retrieval of research data is using observation, interviews and documentation. Data analysis techniques used in this study were data reduction, data presentation, and conclusion. The results of this study indicate that in the learning process at Homeschoolung Pena Surabaya, character values ??emerge which include (1) independent character, responsibility and discipline (2) respect for others, self-confidence, and honesty. Keywords: Education, Character, Homeschooling